2022
DOI: 10.1080/10408363.2022.2038539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age, sex, serostatus, and underlying comorbidities on humoral response post-SARS-CoV-2 Pfizer-BioNTech mRNA vaccination: a systematic review

Abstract: With the advent of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) pandemic, several vaccines have been developed to mitigate its spread and prevent adverse consequences of the Coronavirus Disease 2019 (COVID-19). The mRNA technology is an unprecedented vaccine, usually given in two doses to prevent SARS-CoV-2 infections. Despite effectiveness and safety, inter-individual immune response heterogeneity has been observed in recipients of mRNA-based vaccines. As a novel disease, the specific immu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 89 publications
6
62
3
Order By: Relevance
“…but not Wuhan-Hu-1 after adjusting for known confounders including age, sex assigned at birth, 17 dosing interval, 18 and interval between second vaccination and sample collection (Table S1). 19 These findings suggested that the inoculation order of heterologous vaccines was associated with vaccine-elicited neutralizing antibodies against variant B.1.617.2 but not the ancestral strain.…”
Section: Clinical and Translational Reportmentioning
confidence: 99%
“…but not Wuhan-Hu-1 after adjusting for known confounders including age, sex assigned at birth, 17 dosing interval, 18 and interval between second vaccination and sample collection (Table S1). 19 These findings suggested that the inoculation order of heterologous vaccines was associated with vaccine-elicited neutralizing antibodies against variant B.1.617.2 but not the ancestral strain.…”
Section: Clinical and Translational Reportmentioning
confidence: 99%
“…Furthermore, the two cohorts of patients and volunteers were not optimally matched with regards to both age, sex, and type of COVID-19 vaccine, thereby posing the risk of confounding. It is worthy of note that it has been suggested that male gender relates to lower humoral response to mRNA vaccines [ 39 ]. Nevertheless, we firmly believe that these results represent a real-world scenario advocating for a booster shot in patients with solid neoplastic diseases under systemic treatment, which along with the implementation of protective measures among patients and healthcare providers [ 40 ] could ensure continuity of cancer care during the pandemic [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies have revealed an age, gender and, seronegativity dependence of antibody response against COVID-19. Additional doses of vaccination are recommended for immunocompromised and elderly populations following a combined scheme of mRNA vaccines [ 51 ]. In our study, we confirmed a gender-dependent correlation antibodies with ROS production, both in post-vaccination and COVID-infected individuals.…”
Section: Discussionmentioning
confidence: 99%